Linagliptin and secoisolariciresinol diglucoside attenuate hyperlipidemia and cardiac hypertrophy induced by a high-methionine diet in rats via suppression of hyperhomocysteinemia-induced endoplasmic reticulum stress - Jalal, Israa A.; Elkhoely, Abeer; Mohamed, Shimaa K.; Ahmed, Amany A. E. (Frontiers in Pharmacology, 2023)
Background: Cardiac hypertrophy (CH) is one of the contributing causes of morbidity and mortality. Hyperhomocysteinemia (HHcy) is one of the diseases which may predispose hyperlipidemia and CH. Linagliptin (Lina) and Secoisolariciresinol Diglucoside (SDG) are known to alleviate a variety of illnesses by reducing oxidative stress and inflammation.Aim: This study aimed to study the effect of HHcy on cardiac tissue with a special focus on endoplasmic reticulum (ER) stress as a mainstay pathophysiological pathway. Also, our study examined the protective effect of Lina, SDG, and their combination against HHcy-induced hyperlipidemia and cardiac hypertrophy in rats.Methods: Seventy-five male Sprague Dawley rats were randomly divided into five groups and for 60 days, the following regimen was administered: Group I: rats received distilled water; Group II: rats received Methionine (MET) (2g/kg/day, p.o.); Group III and IV: rats received Lina (3mg/kg/day, p.o.) and SDG (20mg/kg/day, p.o.), respectively followed by MET (2g/kg/day, p.o.); Group V: rats received Lina and SDG followed by MET (2g/kg/day, p.o.).Results: Pretreatment with Lina, SDG, and their combination showed a significant decrease in serum levels of Hcy and an improved lipid profile as compared to the MET-group. Moreover, both drugs improved cardiac injury, as evidenced by the substantial improvement in ECG parameters, morphological features of cardiac muscle, and reduced serum levels of cardiac markers.Additionally, Lina and SDG significantly attenuated cardiac oxidative stress, inflammation, and apoptosis. Furthermore, Lina, SDG, and their combination remarkably downregulated the enhanced expression of E.R. stress markers, GRP78, PERK, ATF-4, CHOP, NF-κB, and SREBP1c as compared to the MET-group.Linagliptin and SDG showed cardioprotective effects against HHcy-induced heart hypertrophy and hyperlipidemia in rats.